Proses Pembuatan Body Pesawat Cesna-172 Dengan Material Komposit - Nanda Dwi Aditya; Sunaryo Sunaryo; Legisnal Hakim (Syntax Literate, 2023)
Composite is a combination of two or more materials that have different phases into a new material and has better properties than both. Composite is an alternative material to replace metal, this is due to the properties of fiber composites which are strong and have a lighter weight than metal (Fahmi, 2011). Composite characteristics are strongly influenced by their constituents, their distribution, and their interactions. More specifically, it is also influenced by the geometry of the reinforcement, where the geometry is the shape, size and size distribution. All of these things were then developed to increase its mechanical characteristics such as strength, rigidity, toughness, performance against heat and others (Sirait, 2010).The manufacture of the Cesna-172 aircraft body uses composite materials with fiber glass. Thus, in each process of making the cesna-172 aircraft body, there are several stages for the manufacture of the aircraft body.